Efficacy and Safety of Immunosuppression Withdrawal in Pediatric Liver Transplant Recipients: Moving Toward Personalized Management. Issue 5 (29th April 2021) - Feng, Sandy; Bucuvalas, John C.; Mazariegos, George V.; Magee, John C.; Sanchez‐Fueyo, Alberto; Spain, Katharine M.; Lesniak, Andrew; Kanaparthi, Sai; Perito, Emily; Venkat, Veena L.; Burrell, Bryna E.; Alonso, Estella M.; et al.
Abstract : Background and Aims: Tolerance is transplantation's holy grail, as it denotes allograft health without immunosuppression and its toxicities. Our aim was to determine, among stable long‐term pediatric liver transplant recipients, the efficacy and safety of immunosuppression withdrawal to identify operational tolerance. Approach and Results: We conducted a multicenter, single‐arm trial of immunosuppression withdrawal over 36‐48 weeks. Liver tests were monitored biweekly (year 1), monthly (year 2), and bimonthly (years 3‐4). For‐cause biopsies were done at investigators' discretion but mandated when alanine aminotransferase or gamma glutamyltransferase exceeded 100 U/L. All subjects underwent final liver biopsy at trial end. The primary efficacy endpoint was operational tolerance, defined by strict biochemical and histological criteria 1 year after stopping immunosuppression. Among 88 subjects (median age 11 years; 39 boys; 57 deceased donor grafts), 33 (37.5%; 95% confidence interval [CI] 27.4%, 48.5%) were operationally tolerant, 16 were nontolerant by histology (met biochemical but failed histological criteria), and 39 were nontolerant by rejection. Rejection, predicted by subtle liver inflammation in trial entry biopsies, typically (n = 32) occurred at ≤32% of the trial‐entry immunosuppression dose and was treated with corticosteroids (n = 32) and/or tacrolimus (n = 38) with resolution (liver tests within 1.5 times the baseline) for all but 1 subject. No death, graft loss, or chronic, severe, or refractory rejection occurred. Neither fibrosis stage nor the expression level of a rejection gene set increased over 4 years for either tolerant or nontolerant subjects. Conclusions: Immunosuppression withdrawal showed that 37.5% of selected pediatric liver‐transplant recipients were operationally tolerant. Allograft histology did not deteriorate for either tolerant or nontolerant subjects. The timing and reversibility of failed withdrawal justifies future trials exploring the efficacy, safety, and potential benefits of immunosuppression minimization.